Effect of hollow bit local exhaust ventilation on respirable quartz dust concentrations during concrete drilling. Issue 5 (4th May 2019) - Rempel, David; Barr, Alan; Cooper, Michael R.
Abstract: Drilling large holes (e.g., 10–20 mm diameter) into concrete for structural upgrades to buildings, highways, bridges, and airport runways can produce concentrations of respirable silica dust well above the ACGIH ® Threshold Limit Value (TLV ® = 0.025 mg/m 3 ). The aim of this study was to evaluate a new method of local exhaust ventilation, hollow bit dust extraction, and compare it to a standard shroud local exhaust ventilation and to no local exhaust ventilation. A test bench system was used to drill 19 mm diameter x 100 mm depth holes every minute for one hour under three test conditions: no local exhaust ventilation, shroud local exhaust ventilation, and hollow bit local exhaust ventilation. There were two trials for each condition. Respirable dust sampling equipment was placed on a "sampling" mannequin fixed behind the drill and analysis followed ISO and NIOSH methods. Without local exhaust ventilation, mean respirable dust concentration was 3.32 (± 0.65) mg/m 3 with a quartz concentration of 16.8% by weight and respirable quartz dust concentration was 0.55 (± 0.05) mg/m 3 ; 22 times the ACGIH TLV. For both LEV conditions, respirable dust concentrations were below the limits of detection. Applying the 16.8% quartz value, respirable quartz concentrations for both local exhaust ventilation conditions were below 0.007 mg/m 3 . There was no difference in respirable quartz dust concentrations between the hollow bit and the shroud local exhaust ventilation systems; both were below the limits of detection and well below the ACGIH TLV. Contractors should consider using either local exhaust ventilation method for controlling respirable silica dust while drilling into concrete.